The psychological impact of COVID-19 pandemic on Iraqi health workers - Riyadh Khudhair Lafta; Nagham A Mawlood (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the psychological impact of coronavirus disease-2019 on frontline healthcare workers in Iraq. Method: The cross-sectional study was conducted from November 2020 to September 2021 after approval from the ethics review committee of the College of Medicine, Mustansiriyah University, Baghdad, Iraq, and comprised doctors and nurses from 4 teaching hospitals and 8 primary healthcare centres in Baghdad. Psychological sequels, like anxiety, depression, fear and insomnia, were assessed along with exposure to coronavirus disease-2019. The study questionnaire was based on the Patient Health Questionnaire Anxiety and Depression Scale. Data was analysed using SPSS 26. Results: Of the 400 participants, 288(72%) were doctors and 112(28%) were nurses. Overall, 215(53.7%) subjects had had a coronavirus disease-2019 infection, 192(48%) reported having anxiety, 148(37%) fear, 100(25%) depressive symptoms, and 51(12.8%) complained of insomnia. Doctors were more likely to have anxiety than nurses (p<0.05), but the difference in terms of depression was not significant (p>0.05). Conclusions: The mental health of the frontline healthcare workers was found to have been affected by the coronavirus disease-2019 pandemic, with anxiety and fear being the main symptoms. Key Words: Depression, Mental Health, Pandemics, Sleep Initiation, Disorders, Anxiety, Fear, Coronavirus